2018
DOI: 10.4012/dmj.2017-084
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i>/<i>in silico</i> investigation of failure criteria to predict flexural strength of composite resins

Abstract: The aim of this study was to investigate a failure criterion to predict flexural strengths of composite resins (CR) by three-dimensional finite element analysis (3D-FEA). Models of flexural strength for test specimens of CR and rods comprising a three-point loading were designed. Calculation of Young's moduli and Poisson's ratios of CR were conducted using a modified McGee-McCullough model. Using the experimental CR, flexural strengths were measured by three-point bending tests with crosshead speed 1.0 mm/min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Instead of in vitro models, in silico three-dimensional finite-element analysis has been used to predict the properties of resin composite materials, such as resin properties with various filler contents 17) or filler sizes 18) . Yamaguchi et al have confirmed that predicted flexural strengths by in silico analysis was significantly correlated to those obtained by in vitro tests 19) . By using nanoscale properties of CAD/CAM RCB components, including the mechanical properties of silica fillers and resin matrices, macroproperties, such as the elastic modulus and Poisson's ratio of the CAD/CAM RCB can be predicted by homogenization analysis 18,20) .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Instead of in vitro models, in silico three-dimensional finite-element analysis has been used to predict the properties of resin composite materials, such as resin properties with various filler contents 17) or filler sizes 18) . Yamaguchi et al have confirmed that predicted flexural strengths by in silico analysis was significantly correlated to those obtained by in vitro tests 19) . By using nanoscale properties of CAD/CAM RCB components, including the mechanical properties of silica fillers and resin matrices, macroproperties, such as the elastic modulus and Poisson's ratio of the CAD/CAM RCB can be predicted by homogenization analysis 18,20) .…”
Section: Introductionmentioning
confidence: 81%
“…The MPS that was used in this study has been reported as a failure criterion to predict flexural strengths for resin composites 19) . All maximum MPS values that were obtained by localization analysis were observed at a hydrolysis layer that excluded the 100% silane coupling model, which suggests that fracture initiation may occur at the location hydrolysis of the silane coupling agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where σt is the tensile stress, P is the load at fracture, π is ratio of the circumference of a circle to its diameter, D is the diameter, and T is the thickness. Flexural strength tests were performed according to the ISO 4049 standard [35]. The cross-sectional area of the samples was 4 mm 2 (sample size: length, 24 mm; height, 2 mm; width, 2 mm).…”
Section: Mechanical Analysis: Curing Depth Hardness Diametral Tensimentioning
confidence: 99%
“…Although FEA is applied within numerous dental investigations, there are only few studies available in this field in which FEA results are compared with real validation experiments 11,12) . Furthermore, FEA is only used in academic research fields and not in daily dental practice under clinically closed conditions.…”
Section: Introductionmentioning
confidence: 99%